Aortic systolic pressure derived with different calibration methods: associations to brachial systolic pressure in the general population. Issue 3 (June 2018) - Wassertheurer, Siegfried; Hametner, Bernhard; Mayer, Christopher C.; Hafez, Ahmed; Negishi, Kazuaki; Papaioannou, Theodore G.; Protogerou, Athanase D.; Sharman, James E.; Weber, Thomas
Abstract : Background: There is increasing evidence that the method of calibration directly influences the association between brachial systolic blood pressure (bSBP) and estimated aortic systolic blood pressure (aSBP) and subsequently affects prognostic and diagnostic differentiation power of the latter. Objective: The aim of this study was to investigate associations between different methods of systolic pressure assessment in a large cohort and its comparison with recently published evidence. Participants and methods: During a public health campaign, cardiovascular hemodynamic data were assessed using a validated oscillometric device in a pharmacy setting. The device measures bSBP, mean arterial pressure, and diastolic blood pressure (DBP), and records brachial waveforms at the DBP level. aSBP1 was derived using bSBP and DBP and aSBP2 using measured mean arterial pressure and DBP for waveform calibration. In addition to pressures, age, sex, and anthropometric data were recorded. Regression analysis was carried out to investigate associations. Results: A total of 7409 (5133/2276, female/male) individuals with a median age of 54 years were sampled. aSBPs differed significantly from bSBP (126.0 mmHg) for aSBP1 (117.0 mmHg) and aSBP2 (127.5 mmHg, both P <0.0001). Regression analysis showed that aSBP2 ( R 2 =0.853) is significantly less associated with bSBP than aSBP1 ( R 2 =0.937) (Williams' test, P <0.001 for comparison). Subgroup analysis showed the major influence of sex and heart rate. The association between bSBP, aSBP1 ( R 2 =0.83), and aSBP2 ( R 2 =0.66), respectively, reduced significantly for borderline hypertensives ( P <0.001 for comparison). Conclusion: In contrast to aSBP1, the association between bSBP and aSBP2 is significantly less dominant and therefore aSBP2 may have potential prognostic superiority over bSBP.